Epistemic ruptures: other narratives to (re) think the habitat - Mattioli, Denise; Solera, Agustina (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2015)
This work intends to engage in dialogue some reflexions coming from the processes of our ongoing research projects related to habitat issues, and the shared discussions within our research team.On this tour merge uncertainties and questions from the process of theatrical-empirical feedback, that is to say, between diverse habitat experiences and theoretical concepts from authors referring to ideas that recognize other ways of producing knowledge, building arguments outside of those established by the western modern and positivist science in Social Studies.In this opening process to recognize other voices, customs, traditions and their way of production and reproduction, based on experiences located, an epistemic break is generated with the hegemonic field.As expressed, we approach the authors allow us to recover the critical to the Modern paradigm, built on a hierarchical relationship of colonial, economic and scientific power; questioning modern conceptions of universality, objectivity and neutrality of knowledge, providing a theoretical device that allows rethink this modern-colonial world system.Then, we attempt to develop other proposals, from the understanding of the local, in order to address located experiences of housing, from a pluriversal knowledge base and alternative epistemological foundations.It is from here that we will be outlining and incorporating new theoretical and methodological elements able to contribute to the construction of alternative epistemological frameworks for the Habitat discipline.